Evidencing the impact of drug store storage conditions on the quality and stability of amoxicillin powders for oral suspension marketed in Peru - Consuelo Del Pilar Vega-Zambrano, León F. Villegas Vílchez& (Journal of Applied Pharmaceutical Science, 2019)
One of the most promising strategies against antimicrobial resistance is to strengthen the monitoring of the quality of medicines in middle- and low-income countries. In Peru, several drug alerts related to quality defects of one of the most commonly used antibiotics, amoxicillin powder for oral suspension, have been reported. This study compared the quality and stability of three amoxicillin powders for oral suspension manufactured by national laboratories and stored for 1 and 3 months in drug stores of populated cities located in the coast, jungle, and the Andes. Esthetic appeal evaluation, delivered volume and pH, and drug content determination were conducted with non-reconstituted and reconstituted samples. In-use stability was also tested after 1 week of refrigeration. All the results were within the specifications of the United States Pharmacopeia for the duration of the study but after 3 months of storage in Tarapoto, clusters formation, smell and taste changes, and a statistically significant reduction in pH and drug content were observed. Based on this and taking also into account the factors affecting the stability of this dosage form of amoxicillin, we can assume these variations are associated with high temperatures and relative humidities during longer periods of storage in drug stores.
Keywords: Powder for oral suspension, reconstitution, amoxicillin, stability, storage conditions.